Topiramate in Pediatric Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Efficacy and tolerability of topiramate in the treatment of pediatric migraine is studied by retrospective analysis of records of 37 children treated at St Christopher's Hospital for Children, Philadelphia, PA.